Boemundo brasileiro: João Ribeiro, cultura cosmopolita, identidade nacional e escrita da história na Primeira República - Barchi, Felipe Yera [UNESP] (Universidade Estadual Paulista (Unesp), 2019)
Esta tese apresenta a trajetória do polígrafo e historiador João Ribeiro (1860-1934) durante a Primeira República Brasileira (1889-1930). Analisando sua biografia e as principais obras pretende-se reavaliar a atuação desse importante homem de letras e suas contribuições à historiografia brasileira de então, bem como sua atuação no Ensino de História, em especial como autor de livros didáticos. Além disso, este estudo põe em foco os debates intelectuais acerca da identidade nacional brasileira em um período marcado pela prevalência de uma cultura cosmopolita nos países ocidentais destacando a contribuição de João Ribeiro para a área.

This thesis presents the trajectory of the polygraph and historian João Ribeiro (1860- 1934) during the First Brazilian Republic (1889-1930). Analyzing his biography and the main works, it is intended to reevaluate the performance of this important man of letters and his contributions to the Brazilian historiography of that time, as well as his performance in History Teaching, especially as author of textbooks. In addition, this study focuses on intellectual debates about Brazilian national identity in a period marked by the prevalence of a cosmopolitan culture in western countries highlighting the contribution of João Ribeiro to the area.
Brazilian Boemund. João Ribeiro, Cosmopolitan Culture, National identity and History’s Writing in Brazilian First Republic
Keywords: João Ribeiro; Cultura Cosmopolita; Identidade Nacional; Historiografia; Livros Didáticos